Effect of Pipe Cutting Gap using CNC toward Surface Hardness - A'rasy Fahruddin (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2018)
This research concerned the standard value of surface roughness on Computer Numerical Control (CNC) to obtain fine pipe cutting result and is more useful for company to simply recognize the appropriate standard gap in designing. Standard design used is 30 mm with 3 specimen variations and variation gap value of 42 mm, 44 mm, and 46 mm. In recognizing fine refinement, standard on Roughness Average (RA) is used with surface roughness scale tool. Based on the experiment, it shows that gap design for pipe with Computer Numeric Control (CNC) in 30 mm has less optimum result because its cutting result still has crust, the gap is still considered too close. Therefore, re-grinding was conducted to result smoother result in achieving surface roughness value of 32RA. Fine pipe result without crust is 46 mm with roughness value of 4 RA. The smaller value obtained from measuring surface roughness, the more optimum result obtained.